Tropics of Teaching : Productivity, Warfare, and Priesthood - Tochon, François Victor, 1954- (Book collections on Project MUSE., 2002)
Based on the premise that deconstruction and demystification are a necessary counterforce to 'shared myths', Tochon offers a provocative assessment of mass educational concepts and teacher education, proposing a rethinking of pedagogy in general.